Coral monitoring in northwest Australia with environmental DNA metabarcoding using a curated reference database for optimized detection. Issue 1 (3rd May 2021) - Dugal, Laurence; Thomas, Luke; Wilkinson, Shaun P.; Richards, Zoe T.; Alexander, Jason B.; Adam, Arne A.S.; Kennington, W. Jason; Jarman, Simon; Ryan, Nicole M.; Bunce, Michael; Gilmour, James P.
Abstract: The need for efficient and more accurate ways of monitoring threatened ecosystems is becoming increasingly urgent as climate change intensifies. Coral reefs are an example of an ecosystem in crisis, with widespread declines in coral cover and diversity documented over recent decades. Novel molecular approaches such as biomonitoring using environmental DNA (eDNA) from seawater samples show great potential to complement future coral reef monitoring programs, especially when used in combination with conventional methods. However, eDNA metabarcoding studies often rely on public databases (e.g., GenBank) for assigning taxonomy, which generally limits the number of sequences that can be taxonomically identified. The extent to which building reference tissue sequences improves taxonomic resolution has yet to be fully examined. Here, we combined traditional coral reef monitoring data with eDNA assessments derived from seawater collected at the highly diverse Rowley Shoals in Western Australia. Using two ITS2 assays developed to target basal metazoan DNA and a reference database spiked with 70 local coral specimens, we identified 37 genera and 40 species from 56 1 L seawater samples. We identified considerable overlap of taxa with visual survey data and showed that assignment of amplicon sequence variants was significantly improved when "spiking" the taxonomic classifier with curated sequences of locally collected species. Our findings showcase the potential of eDNA metabarcoding for monitoring the biodiversity of reef corals and highlight the importance of custom reference sequence databases for improving taxonomic resolution in metabarcoding studies. Abstract : In this study, we applied eDNA metabarcoding using two ITS2 assays to detect coral diversity at a remote atoll system in Northwest Australia. We compared eDNA results to those originating from traditional visual surveys and found considerable overlap in the genus diversity recorded. We also show that by curating a reference database containing 70 local coral species, we increased by more than 2.3 fold the number of species‐level detections recovered. ​